The impact of health education videos on the level of knowledge and attitudes of pregnant women about danger signs in pregnancy - Nisman, Wenny Artanty; Khoironi, Nur Cahya; Haryani, Oktavia Dwi (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: Complications of pregnancy can cause morbidity and mortality. Pregnant women should know about these complications so that they can immediately get intervention. Some of these complications are referred to as danger signs of pregnancy. The aim of the paper to know the effect of health education videos on the level of knowledge and attitudes about danger signs in pregnancy.Methods: This quasi-experimental study used a nonequivalent pretest-posttest with control group design. This research was conducted at Jetis Public Health Center (PHC) (intervention group) and Pajangan PHC (control group). The number of respondents was 64 pregnant women. The control group received education with the Maternal and Child Health (MCH) handbook while the intervention group also received education using MCH handbook and education using videos about the danger signs of pregnancy. An educational video with a duration of 10 minutes 19 seconds contains about danger signs of pregnancy and actions that must be taken to overcome these problems. Educational videos were given to respondents via Android phones that can be watched repeatedly. data analysis has been carried out with the t test.Results: Based on the homogeneity test on the characteristic data between the intervention and control group were homogeneous. Comparison between the difference the knowledge of the pre-posttest in the intervention group compared to the difference the pre-posttest knowledge of the control group (8.59 vs. 0.31) with p value = 0.311, meaning that there is no effect of providing education with video on knowledge. Comparison between the difference in pre-posttest attitudes of the intervention group compared with the difference in pre-posttest attitudes of the control group (1.71 vs -1.21) p value = 0.001, meaning that there is an effect of providing education with video on attitudes.Conclusion: Health education videos can improve the attitude about the danger signs of pregnancy.